Perbandingan Persepsi Remaja Anak Petani dan Bukan Anak Petani Terhadap Profesi Petani di Desa Tegallinggah, Kecamatan Karangasem, Kabupaten Karangasem - ZUFARI, FAWWAZ ALDI; ASTITI, NI WAYAN SRI; PUTRA, I GEDE SETIAWAN ADI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2023)
Comparison Of The Perceptions Of Adolescent Farmers’ Children And Non-Farmers’ Children Towards The Farming Profession in Tegallinggah Village, Karangasem District, Karangasem Regency.  Bali Province is a province that is experiencing rapid development in the industrial sector or the service and tourism sector. Problems in the field of agricultural labor still continue today. Changes in demographic structure that are slightly favorable in the agricultural sector are the main problem, namely that the number of old farmers is getting higher, while the young labor force is decreasing. The sample in this study was 74 people, then divided into two sample groups, namely 37 adolescents of farmer children and 37 adolescents of non-farmer children. Determination through  simple random sampling method,  data collection using survey methods and data analysis using statistical descriptive analysis. The results of this study show that adolescents' perception of the farmer profession in Tegallinggah Village belongs to the category of hesitating, they think of farmers as a fairly good profession, but when compared to other professions, there are still many professions that are considered better than the farmer profession. Other results of this study show that there are differences in the perceptions of adolescents of farmer children with adolescents of non-farmer children, where the perception of adolescents of farmer children is better than the perception of adolescents not children of farmers. The suggestion in this study, the agriculture office of Karangasem Regency can provide counseling on the potential and opportunities related to the farmer profession.